2014
DOI: 10.1089/gtmb.2014.0004
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms and Febrile Neutropenia in Acute Leukemia—No Association with IL-4, CCR-5, IL-1RA, but the MBL-2, ACE, and TLR-4 Are Associated with the Disease in Turkish Patients: A Preliminary Study

Abstract: Although TLR-4, ACE, and MBL-2 GPs have been extensively investigated in different clinical pictures, this is the first study to evaluate the role of these polymorphisms in the genetic etiopathogenesis of FN in patients with ALs. As a conclusion, TLR-4, ACE, and MBL-2 genes might play roles in the genetic etiopathogenesis of FN in patients with ALs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…Our results consistent with results obtained by Pehlivan et al [30] which show that Gram-negative bacteremia was more common in deficient MBL2 AB/BB genotype. However our result inconsistent with study by Hellemann et al [31] in critically ill patients admitted to an intensive care, which reported an association of low MBL2 O/O genotype with an increased incidence of Gram-positive infections.…”
Section: Discussionsupporting
confidence: 93%
“…Our results consistent with results obtained by Pehlivan et al [30] which show that Gram-negative bacteremia was more common in deficient MBL2 AB/BB genotype. However our result inconsistent with study by Hellemann et al [31] in critically ill patients admitted to an intensive care, which reported an association of low MBL2 O/O genotype with an increased incidence of Gram-positive infections.…”
Section: Discussionsupporting
confidence: 93%
“…This could have affected the quality of their study if the episodes occurred within a short period of time (i.e. biomarker had not returned to baseline levels) or there was overrepresentation of patients with genetic predisposition to infections, in their biomarker response, or fever without adverse outcome …”
Section: Discussionmentioning
confidence: 99%
“…Several innate immune factors have been proposed as possible determinants of infectious morbidity in patients receiving chemotherapy. Among these are mannose-binding lectin (MBL2), ficolin, TLR-4 (135,145) and NOD2 (220). Much research has been done for MBL but the evidence for effects of MBL deficiency remains conflicting (7,46,55,62,101,105,116,139,142).…”
Section: Cim Diagnosis and Biomarkers Supported By Animal Modelsmentioning
confidence: 99%